Serum c-reactive protein as a predictive factor for spontaneous stone passage in patients with 4 to 8 mm distal ureteral stones - Mohammad, Ehab Jasim; Abbas, Kanaan Mahdi; Hassan, Anas Falah; Abdulrazaq, Alaa Abdulqader (International Surgery Journal, 2018)
Background: Ureteral stones are common problems in daily emergency department practice. Ureteric stone is responsible for 20%. Ureter obstruction caused by a ureteral stone triggers inflammatory changes in the proximal submucosal layer and prevents passage of the stone. C reactive protein (CRP) was found to be an indicator of ureteral stone outcome. The objective of this study was to measure serum CRP for patients with 4-8 mm distal ureteric stone and use its level as predictive factor for spontaneous stone passage. Methods: A prospective study was designed on a total of 73 patients (M=34; F=39) who were in the age group (18-50) years, who presented with ureteral colic secondary to a solitary unilateral, 4 to 8 mm distal ureteral stone. Patients were grouped according to spontaneous stone passage. The patients were selected at the urology unit, in Ghazi AL Hariri Hospital for Specialized Surgery, Medical City Complex in Baghdad from October 2014 till October 2016. The follow up continued until the stone spontaneously passed, as reported by the patient, or for a maximum period of 4 weeks. Results: Age, BMI, and gender did not show significant difference between the two groups ;30 have spontaneous stone passage (SSP), and 43 no spontaneous stone passage (no SSP). Stone size is significantly higher in the group without SSP their median is 6 mm compared to 4 mm for SSP group. CRP is significantly elevated in no SSP group compared to SSP. CRP, stone size and previous history of stone passage was the only significant and independent predictors of SSP (low CRP, low stone size, and positive history predict SSP). Conclusions: Stone size, CRP, previous Hx of stone passage are independent predictors for SSP. Measuring serum CRP levels is useful for predicting whether spontaneous ureteral stone passage will be successful. More aggressive treatment methods such as URS should be considered when serum CRP levels is high.